1999
DOI: 10.1517/13543784.8.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Levobupivacaine: a new safer long acting local anaesthetic agent

Abstract: The choice of local anaesthetic is influenced by several factors; it must provide effective anaesthesia and analgesia for the duration of the procedure and meet the expectations for post-operative pain management. Of primary concern is patient safety. Bupivacaine, currently the most widely used long acting local anaesthetic agent in both surgery and obstetrics, generally has a good safety record but its use has resulted in fatal cardiotoxicity, usually after accidental intravascular injection. Hence, for sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 18 publications
0
50
0
3
Order By: Relevance
“…4 Although, levobupivacaine has very similar pharmacological properties to racemic bupivacaine, it is noted for lower toxicity. 5 In present study in Tables 1-4 we have compared the two forms of bupivacaine and found in Table 5, that incidence of side effects especially hypotension was observed. Hypotension was observed in 2 and 3 cases of Group L and Group R respectively.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…4 Although, levobupivacaine has very similar pharmacological properties to racemic bupivacaine, it is noted for lower toxicity. 5 In present study in Tables 1-4 we have compared the two forms of bupivacaine and found in Table 5, that incidence of side effects especially hypotension was observed. Hypotension was observed in 2 and 3 cases of Group L and Group R respectively.…”
Section: Discussionmentioning
confidence: 67%
“…3 Many drugs including epinephrine, opioids, clonidine, ketamine, midazolam and neostigmine have been tried as adjuvants with caudal bupivacaine to improve the quality of analgesia and extend its duration but each of these has its own documented adverse effects. [4][5][6] The primary aim of this study was to compare the pharmacological anaesthetic efficacy of levobupivacaine with bupivacaine and observe the risk of cardiotoxicity and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Levobupivacaine is a longlasting LA with an S(-) isomer of bupivacaine and an amide structure. As with all LA agents, levobupivacaine functions by altering voltage-sensitive channels in neural membranes (3). Understanding the histopathological effects of intraarticularly injected LAs is critical as they may alter the joint cartilage and the synovium (5).…”
Section: Introductionmentioning
confidence: 99%
“…Levobupivacaine is a long-acting local anesthetic in common use, and as a single enantiomer of bupivacaine (rather that a racemic mixture), it has a relatively low risk of cardiac and central nervous system side effects [6,12]. However, as all previous studies used combinations of agents, it is unclear whether isolated use of periarticular infiltration of a local anesthetic agent at the time of surgery provides pain relief or reduces the frequency of complications.…”
Section: Introductionmentioning
confidence: 99%